Genetic analysis and trait associations for yield and quality in the BC2F3 generation of rice (Oryza sativa L.) - Kadthala, Bhargava; Sreedhar, M; Jhansi, Lakshmi V; Ramya, Rathod; Parimala, K; Pushpavalli, S N C V L; Vanisri , S (Plant Science Today, 2026)
This study evaluated genetic variation, heritability, genetic advance and trait relationships among yield, yield-related attributes and physical grain quality characteristics in 56 BC2F3 progenies derived from a cross between Telangana Sona (TS) and an Assam landrace 10-3. The lines carrying the brown planthopper (BPH) resistance QTL qbph-1-1 were assessed along with parents and two high-yielding checks (KNM 1638 and JGL 3844) in an alpha lattice design at Regional Sugarcane and Rice Research Station (RR & RRS), Rudrur, Nizamabad, during the Rabi, 2022-23. ANOVA revealed significant variation for agro-morphological and grain quality traits. High genotypic and phenotypic coefficients of variation were recorded for kernel breadth and high heritability coupled with high genetic advance was recorded for panicle length, 1000-seed weight, grain yield per plant and kernel breadth, indicating additive gene action. Grain yield per plant showed significant positive association with number of tillers per plant, number of productive tillers per plant, panicle length and number of filled grains per panicle. Based on superior yield performance relative to the best check, reduced plant height and resemblance to Telangana Sona in maturity and grain traits, 12 BC2F3 lines were shortlisted for further physical, chemical and cooking quality analyses. Among them, three lines exhibited favorable cooking and chemical quality parameters, demonstrating grain quality comparable to Telangana Sona. These findings highlight the potential of these lines for further evaluation in advanced yield trials and release.